2021
DOI: 10.3389/fnut.2021.744187
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Adipose Tissue Characteristics and Metabolic Flexibility in Humans: A Systematic Review

Abstract: Adipose tissue total amount, distribution, and phenotype influence metabolic health. This may be partially mediated by the metabolic effects that these adipose tissue characteristics exert on the nearby and distant tissues. Thus, adipose tissue may influence the capacity of cells, tissues, and the organism to adapt fuel oxidation to fuel availability, i.e., their metabolic flexibility (MetF). Our aim was to systematically review the evidence for an association between adipose tissue characteristics and MetF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Changes in FM were positively associated with changes in postprandial lipid oxidation, while postprandial carbohydrate oxidation and postprandial ∆RQ were negatively correlated. A recent systematic review 47 that combined clinical studies on the relationship between adiposity and ∆RQ in response to metabolic challenges reported inverse correlations between ∆RQ to glucose plus insulin stimulation (i.e., measured during a hyperinsulinemic-euglycemic clamp) and total FM, visceral adipose tissue, and waist circumference. However, the authors found no association between adipose tissue characteristics and postprandial ∆RQ in response to dietary challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in FM were positively associated with changes in postprandial lipid oxidation, while postprandial carbohydrate oxidation and postprandial ∆RQ were negatively correlated. A recent systematic review 47 that combined clinical studies on the relationship between adiposity and ∆RQ in response to metabolic challenges reported inverse correlations between ∆RQ to glucose plus insulin stimulation (i.e., measured during a hyperinsulinemic-euglycemic clamp) and total FM, visceral adipose tissue, and waist circumference. However, the authors found no association between adipose tissue characteristics and postprandial ∆RQ in response to dietary challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in FM were positively associated with changes in postprandial lipid oxidation, while postprandial carbohydrate oxidation and metabolic flexibility were negatively correlated. A recent systematic review 58 that combined clinical studies on the relationship between adiposity and metabolic flexibility reported inverse correlations between metabolic flexibility to glucose plus insulin stimulation (i.e., measured during a hyperinsulinemic euglycemic clamp) and total FM, visceral adipose tissue, and waist circumference. However, the authors found no association between adipose tissue characteristics and metabolic flexibility in response to dietary challenges.…”
Section: The Inter-relationships Between Metabolic Flexibility Body C...mentioning
confidence: 99%
“…In addition, it was found to be impaired in individuals with obesity and T2D compared to lean and healthy individuals [ 9 , 10 ]. Assessment of metabolic flexibility can be conducted through postprandial changes (following a meal or any other insulin stimulation) in the respiratory exchange ratio (RER) from the metabolic cart [ 11 , 12 ], which estimates the body’s preference for macronutrient oxidation. Accordingly, several studies showed different RER responses between participants with high metabolic flexibility compared with participants with low flexibility for fasting, a high-carbohydrate diet, and a high-fat diet [ 13 ].…”
Section: Introductionmentioning
confidence: 99%